Quality of care and its determinants in longer term mental health facilities across Europe; a cross-sectional analysis - Killaspy, Helen; Cardoso, Graça; White, Sarah; Wright, Christine; Caldas de Almeida, José Miguel; Turton, Penny; Taylor, Tatiana L; Schützwohl, Matthias; Schuster, Mirjam; Cervilla, Jorge A; Brangier, Paulette; Raboch, Jiri; et al. (BMC psychiatry, 2016)
BACKGROUND: The Quality Indicator for Rehabilitative Care (QuIRC) is an international, standardised quality tool for the evaluation of mental health facilities that provide longer term care. Completed by the service manager, it comprises 145 items that assess seven domains of care: living environment; treatments and interventions; therapeutic environment; self-management and autonomy; social interface; human rights; and recovery based practice. We used the QuIRC to investigate associations between characteristics of longer term mental health facilities across Europe and the quality of care they delivered to service patients. METHODS: QuIRC assessments were completed for 213 longer term mental health units in ten countries that were at various stages of deinstitutionalisation of their mental health services. Associations between QuIRC domain scores and unit descriptive variables were explored using simple and multiple linear regression that took into account clustering at the unit and country level. RESULTS: We found wide variation in QuIRC domain scores between individual units, but across countries, fewer than a quarter scored below 50 % on any domains. The quality of care was higher in units that were smaller, of mixed sex, that had a defined expected maximum length of stay and in which not all patients were severely disabled. CONCLUSIONS: This is the first time longer term mental health units across a number of European countries have been compared using a standardised measure. Further use of the QuIRC will allow greater understanding of the quality of care in these units across Europe and provide an opportunity to monitor pan-European quality standards of care for this vulnerable patient group.
Keywords: průřezové studie; Quality Indicators, Health Care; Cross-Sectional Studies; Quality Assurance, Health Care; Mental Disorders; Deinstitutionalization; ústavy pro duševně nemocné; lidé; Hospitals, Psychiatric; služby péče o duševní zdraví; Europe; Mental Health; mužské pohlaví; dlouhodobá péče; Female; duševní poruchy; ukazatele kvality zdravotní péče; deinstitucionalizace; Male; ženské pohlaví; Long-Term Care; péče o sebe; Humans; Mental Health Services; Self Care; Evropa; zajištění kvality zdravotní péče; duševní zdraví